2022
DOI: 10.1007/s11904-022-00622-0
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Vaccine Hesitancy for Future COVID-19 and HIV Vaccines: Lessons from Measles and HPV Vaccines

Abstract: Background The discovery of vaccines significantly reduced morbidity and mortality of infectious diseases and led to the elimination and eradication of some. Development of safe and effective vaccines is a critical step to the control of infectious diseases; however, there is the need to address vaccine hesitancy because of its potential impact on vaccine uptake. Methods We conducted a narrative review of studies on interventions to address measles and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 162 publications
1
10
0
Order By: Relevance
“…These stakeholders play a critical role in providing education, recommendations, and reminders about vaccination to people and communities to drive willingness and uptake of vaccines. Previous studies of other recommended vaccines have shown that the involvement of healthcare professionals in policy-making decisions regarding vaccine implementation, and the use of educational interventions in healthcare settings, can be effective in overcoming vaccine hesitancy [ 64 , 65 ]. Further investigation is required to understand the specific drivers and barriers for these stakeholders to advocate the importance of vaccination against dengue in each individual country context.…”
Section: Discussionmentioning
confidence: 99%
“…These stakeholders play a critical role in providing education, recommendations, and reminders about vaccination to people and communities to drive willingness and uptake of vaccines. Previous studies of other recommended vaccines have shown that the involvement of healthcare professionals in policy-making decisions regarding vaccine implementation, and the use of educational interventions in healthcare settings, can be effective in overcoming vaccine hesitancy [ 64 , 65 ]. Further investigation is required to understand the specific drivers and barriers for these stakeholders to advocate the importance of vaccination against dengue in each individual country context.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy is not only a behavioral problem and complex social phenomenon [ 45 ]. The interventions in physical exercise and influenza megastudies focus on the gap between intention and action [ 29 ]. Interventions in two megastudies for behavior change were mainly “Nudges”: planning, bonus, exercise commitment contracts, sharing social values or norms in the community, fitness questionnaires, and different urging messages [ 38 , 40 ].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Among those concerned about vaccine safety, some are concerned about additional risks because of their clinical conditions, such as pregnant women [ 16 , 30 ], the elderly [ 16 , 48 ], and patients with chronic diseases [ 49 , 50 ]. In recent years, vaccine hesitancy has closely been related to widespread rumors about infertility or autism, which proved totally false [ 29 ]. In addition, suspicion of vaccine effectiveness matters in vaccine hesitation, especially facing a new vaccine, the vaccine does not work as expected or few studies have been conducted to demonstrate its efficacy and safety in specific populations at risk [ 46 , 51 , 52 , 53 ].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
See 2 more Smart Citations